Mitochondrial repair as potential pharmacological target in cerebral ischemia - Kaur, Ms. Mandeep; Sharma, Dr. Saurabh (Mitochondrion, 2022)
[Display omitted] Cerebral ischemia and its consequences like transient ischemic attack, aneurysm and stroke are the common and devastating conditions which remain the leading cause of mortality after coronary heart disease in developed countries and are the greatest cause of disability, leaving 50% of survivors permanently disabled. Despite recognition of risk factors and mechanisms involved in the pathology of the disease, treatment of ischemic disorders is limited to thrombolytic drugs like recombinant tissue plasminogen activator (rt-PA) and clinical rendition of the neuroprotective agents have not been so successful. Recent studies evidenced the role of mitochondrial dysfunction in neuronal damage that occurred after cerebral ischemia. This review article will focus on the various fundamental mechanisms responsible for neuronal damage because of mitochondrial dysfunction including cell signaling pathways, autophagy, apoptosis/necrosis, generation of reactive oxygen species, calcium overload, the opening of membrane permeability transition pore (mPTP), mitochondrial dynamics and biogenesis. Recent studies have concerned the significant role of mitochondrial biogenesis in mitochondrial repair and transfer of healthy mitochondria from astrocytes to the damaged neurons, providing neuroprotection and neural recovery following ischemia. Novel and influential studies have evidenced the significant role of mitochondria transfer and mitochondrial transplantation in reviving cell energy and in replacement of impaired or dysfunctional mitochondria with healthy mitochondria after ischemic episode. This review article will focus on recent advances in mitochondrial interventions and exogenous therapeutic modalities like mitochondria transfer technique, employment of stem cells, mitochondrial transplantation, miRNA inhibition and mitochondrial-targeted Sirtuin1 activator for designing novel and promising treatment for cerebral ischemia induced pathological states.